2011
DOI: 10.1152/ajpregu.00772.2010
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate enhances myosin-powered actin filament velocity under acidic conditions in a motility assay

Abstract: Debold EP, Turner MA, Stout JC, Walcott S. Phosphate enhances myosin-powered actin filament velocity under acidic conditions in a motility assay. Am J Physiol Regul Integr Comp Physiol 300: R1401-R1408, 2011. First published February 23, 2011 doi:10.1152/ajpregu.00772.2010.-Elevated levels of inorganic phosphate (Pi) are believed to inhibit muscular force by reversing myosin's force-generating step. These same levels of Pi can also affect muscle velocity, but the molecular basis underlying these effects remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(109 citation statements)
references
References 38 publications
7
102
0
Order By: Relevance
“…Based on in vitro motility experiments, Debald et al [15,16] suggest that low pH and high Pi modify rate of breaking of A-M linkages, and can cause inhibition of either P o and V max depending on experimental conditions. As pointed out by Sugi et al [17], however, the state of contractile proteins in vitro experiments differs too far from those in muscle and their explanation is far from being conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on in vitro motility experiments, Debald et al [15,16] suggest that low pH and high Pi modify rate of breaking of A-M linkages, and can cause inhibition of either P o and V max depending on experimental conditions. As pointed out by Sugi et al [17], however, the state of contractile proteins in vitro experiments differs too far from those in muscle and their explanation is far from being conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with skinned muscle fibers have shown that low pH (~6.5) has only a small effect on Po, but significantly reduces V max [5,9]. Because of the importance of studying the effect of increased Pi and low pH on in vitro ATP-dependent actinmyosin sliding have been performed intensively [12][13][14][15][16] at micromolar range of ATP concentration. Though their work is interesting, the experimental conditions of their experiments differ to far from the physiological condition in muscle.…”
Section: Introductionmentioning
confidence: 99%
“…For the in vitro motility assays described below, both myosin and actin were isolated from chicken pectoralis tissue as described previously (25). Actin was purified from chicken pectoralis muscle using the methods described by Pardee and Spudich (26) with minor modifications as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…Actin was purified from chicken pectoralis muscle using the methods described by Pardee and Spudich (26) with minor modifications as described previously (25). The isolated filamentous actin was stabilized and labeled fluorescently by incubating it overnight at 4°C with TRITC/ phalloidin (Sigma-Aldrich) as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
“…For the in vitro motility of troponin-tropomyosin-regulated thin (i.e., actin-containing) filaments propelled by skeletal muscle myosin, Debold et al (28) found that n max and f mot of fully activated (high Ca 2þ ) thin filaments did not change upon addition of 30 mM P i ([ATP] ¼ 2 mM). While thin filament regulation could affect the regulation of myosin kinetics by P i , full activation by Ca 2þ should return the kinetics to those of unregulated actin filaments.…”
Section: Experimental Observationsmentioning
confidence: 99%